2020
DOI: 10.1099/mic.0.000943
|View full text |Cite
|
Sign up to set email alerts
|

MifS, a DctB family histidine kinase, is a specific regulator of α-ketoglutarate response in Pseudomonas aeruginosa PAO1

Abstract: The C5-dicarboxylate α-ketoglutarate (α-KG) is a preferred nutrient source for the opportunistic pathogen Pseudomonas aeruginosa . However, very little is known about how P. aeruginosa detects and responds to α-KG in the environment. Our laboratory has previously shown that the MifS/MifR two-component signal transduction system regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Lastly, the MifSR TCS affects microcolony and cluster formation during the last stages of the biofilm maturation process. Upon sensing α-ketoglutarate, the HK MifS phosphorylates MifR, which acts as an EBP, assisting the σ 54 factor RpoN to bind to the promoter region of α-ketoglutarate transport genes [27,149]. α-ketoglutarate is a preferred carbon source for P. aeruginosa, and it is required for virulence in pathogenic bacteria [149].…”
Section: Gacs-gacamentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the MifSR TCS affects microcolony and cluster formation during the last stages of the biofilm maturation process. Upon sensing α-ketoglutarate, the HK MifS phosphorylates MifR, which acts as an EBP, assisting the σ 54 factor RpoN to bind to the promoter region of α-ketoglutarate transport genes [27,149]. α-ketoglutarate is a preferred carbon source for P. aeruginosa, and it is required for virulence in pathogenic bacteria [149].…”
Section: Gacs-gacamentioning
confidence: 99%
“…Upon sensing α-ketoglutarate, the HK MifS phosphorylates MifR, which acts as an EBP, assisting the σ 54 factor RpoN to bind to the promoter region of α-ketoglutarate transport genes [27,149]. α-ketoglutarate is a preferred carbon source for P. aeruginosa, and it is required for virulence in pathogenic bacteria [149]. MifR has also been shown to alter the production of at least 18 proteins when mutated or overexpressed, many of which are involved in growth under anaerobic conditions, suggesting a link between biofilm formation and oxygen restriction [42].…”
Section: Gacs-gacamentioning
confidence: 99%
“…The MifSR TCS was originally identified for its role in microcolony formation and named accordingly [ 12 ]. It was later demonstrated that the MifSR TCS is required for the utilization of C 5 -dicarboxylates such as α-ketoglutarate (α-KG) in which MifR activates transcription of the PA5530 gene, encoding for a C 5 -dicarboxylate-proton symporter [ 13 15 ]. The utilization of C 4 - and C 5 -dicarboxylates as a sole carbon source in P. aeruginosa PAO1 is dependent on DctD and MifR, respectively [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sensor has two transmembrane domains, between which is a structured periplasmic domain that binds directly the molecule to be sensed, which results in the transduction of this signal through the membrane to the transmitter domain in the cytoplasm. Zaara Sarwar from The College of New Jersey, USA, working with the group of Christopher Nomura at the State University of New York, Syracuse, USA, has been looking at the function of MifS and has found that it is highly specific for α-KG and only recognizes the related C5-dicarboxylate glutarate [ 17 ]. There are structures of similar sensing domains such as the Vibrio cholerae DctB protein, which adopts α/β PDC fold [ 18 ], and the authors modelled the MifS sensing domain on these.…”
mentioning
confidence: 99%